1993
DOI: 10.1007/bf01212725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment with LHRH analogs containing cytotoxic radicals on the binding characteristics of receptors for luteinizing-hormone-releasing hormone in MXT mouse mammary carcinoma

Abstract: Binding capacities and apparent dissociation constants of receptors for luteinizing-hormone-releasing hormone (LHRH) were investigated in estrogen-independent MXT mammary cancers of untreated mice and after in vivo treatment with agonistic or antagonistic analogs of LHRH containing cytotoxic radicals: AJ-04 (agonist [D-Lys6]LHRH linked to methotrexate), T-98-([D-Lys6]LHRH coupled to glutaryl-2-(hydroxmethyl)anthraquinone (G-HMAQ)) and T-121/B (LHRH antagonist T-147 containing two residues of G-HMAQ), which ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
6
8
0
Order By: Relevance
“…In this study we also showed that LH-RH analogs decreased binding capacity of EGF receptors on tumor cells. This finding is in agreement with previous studies [30]. The cytotoxic analog was more effective than [D-Lys6]LH -RH in producing a down-regulation of EGF receptors.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In this study we also showed that LH-RH analogs decreased binding capacity of EGF receptors on tumor cells. This finding is in agreement with previous studies [30]. The cytotoxic analog was more effective than [D-Lys6]LH -RH in producing a down-regulation of EGF receptors.…”
Section: Discussionsupporting
confidence: 95%
“…These receptors can mediate antitumor effects of LH-RH analogs. In several earlier studies, we have shown the presence of receptors for LH-RH in MXT breast cancers [12,13,30]. In this study, the finding that labeled T-98 accumulated in MXT tumors 3 hours after s.c. injection shows that specific targeting might play a role in the enhanced effect of cytotoxic analog T-98.…”
Section: Discussionmentioning
confidence: 54%
“…Binding affinity of cytotoxic LH-RH analog T-98 was essentially identical in both equilibrium and kinetic experiments. Equilibrium homologous displacement of [D-Trp6]LH-RH and T-98 using human breast tumor membranes confirmed present kinetic data as well as our previous results [23,24,27] that [DTrp~]LH-RH in human breast cancer membranes binds to two classes of receptors. In rat pituitary superfusion systems T-98 was shown to be a powerful analog in a wide range of doses [19].…”
Section: Binding Characteristics Of Several New Cytotoxic Lh-rh Analosupporting
confidence: 77%
“…Receptors for LH-RH were previously found in human breast cancer as well as in estrogen dependent and estrogen independent MXT mammary cancers [12,13,15,[23][24][25][26][27][28]. Our kinetics experiments presented herein, suggest that cytotoxic LH-RH analogs bind to two classes of receptors in membranes of human breast cancer.…”
Section: Binding Characteristics Of Several New Cytotoxic Lh-rh Analomentioning
confidence: 66%
See 1 more Smart Citation